ANALYSIS OF INCIPIENT SLIDING CONTACT BY 3-DIMENSIONAL LINEAR COMPLEMENTARITY-PROBLEM FORMULATION - LEE, SC; KWAK, BM; KWON, OK (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
A numerical scheme is developed for the analysis of incipient sliding contact problems with an orthotropic friction law of the Coulomb type. Using the polyhedral friction law as a linearization of elliptical friction domain, a three-dimensional linear complementarity problem (LCP) formulation in an incremental form is obtained, and an equivalent minimization problem is accordingly derived. A Lemke's complementary pivoting algorithm is used for solving the LCP. The scheme is illustrated by spherical contact problems and the effects of eccentricity of elliptical friction domain on the traction and slip are discussed.